Perceptions of social development by senior officials in the National Department of Social Development, South Africa. - Mohamed, Zaheera (My University, 2011)
The primary purpose of this study was to ascertain how senior government officials employed within the Department of Social Development in South Africa perceived the social development approach to social welfare. The study was confined to the national Department of Social Development and nine senior government officials were interviewed, all of them employed in different work streams but related to social development policy development. A semi-structured interview schedule comprising of open-ended questions was utilised to collect information. A deductive thematic analysis was used to analyse the data. The main findings that emerged from the study were that senior managers employed within the national Department of Social Development had a good understanding of the social development approach to social welfare. They were familiar with the key characteristics, goals, strategies and linkages between social and economic development. Senior government officials also noted progress with the implementation of the social development approach and identified that social policies were largely aligned to this approach. In terms of challenges, senior government officials identified a range of challenges impacting on the implementation of the social development approach and this ranged from the lack of a common understanding of social development within broader government, inappropriate social service workforce, poor coordination and integration, inadequate leadership and an inadequate monitoring and evaluation system to measure social development progress. Senior government officials identified a range of suggestions to improve on the implementation of the social development approach. One of the suggestions was the development of an overarching social development strategic framework to guide the social development approach and acknowledge it as government’s chosen approach to social welfare. Many suggestions related to enhancing the capabilities of social service professionals and this included the development of a social service policy framework, enhanced engagement between higher education institutions and the Department of Social Development to ensure relevant curriculum. The findings of the study recommends a series of interventions to be implemented by the national Department of Social Development such as the development of an overarching social development strategic framework as suggested by senior government officials, an audit of policies to assess alignment with the social development approach and a review of its’ consultation processes. The findings of the study identify a need to replicate this research at provincial level to ascertain how the social development approach is understood and implemented at the point of service delivery.
Keywords: Social development; Perception; Senior government officials; Implementation; Challenges; Suggestions